Caracterização da língua portuguesa da segunda metade do século XIX na região da fronteira (Santana do Livramento/ Rivera) - Pereira, Veridiana Veleda (2017)
The purpose of the following work is to investigate the characteristics of the Portuguese language in the second half of the nineteenth century, in the border region between Santana do Livramento (Brazil) and Rivera (Uruguay) based on a collation of documents collected from the David Canabarro museum in Santana do Livramento city. To carry out the research we start from the theory of Historical Sociolinguistics, and since the studies based on this perspective are recent, we present some theoretical questions based on authors just as Vera do Prado Lima Albornoz (s/d) who addresses the history of border formation; Juan Camilo Conde Silvestre (2007) who addresses in his studies the emergence and development of the Historical Sociolinguistics perspective; Rosa Virginia Matos e Silva (2008), who works with the perspective of historical linguistics; Weinreich, Labov, Herzog (2006) that address the relation between language, subject and History and Dorotea Frank Kersch (2011) who studies the linguistic contact in the border region and languages and identities in the border context.The documents were initially separated by genre, and since one of the initial objectives is to observe possible influences of the Spanish language in the Portuguese language we have classified the documents by date criteria, once that in 1867 Rivera city is inaugurated right in front of Santana do Livramento's territory, making possible the linguistic contact between Portuguese and Spanish in that region. Based on this classification, 37 documents with a total of 112 folios were analyzed. As big part of the documents that compose this collect are of official character it was made necessary to also address the importance of this kind of document and its contribution for a linguistic study through the social historical perspective. The facsimile official documents were edited in diplomatic edition and analyzed according to the number of occurrences of phonological phenomena just as:elision, proclisification, enclitisation, deletion, raise, vocalic harmony, subsidence, hypersegmentation and hyposegmentation. After this data survey we created a line that indicates which genres present less or more incidence of forms that can represent phonological phenomena constituting a gradient in the permeability of the text in relation to the phonological phenomena. Lastly, linguistic phenomena that accuse the influence of Spanish language on Portuguese language were not identified, since the official documents present a writing model, many times pre-ready, that does not allow to observe particularities of other language influences in the writing of the scribe.